Value For Money Time And Legitimation - Umi Novia Sani; Siti Nurhaliza Harahap; Nurlalila Nurlalila; Pipit Nopita (Proceeding International Seminar of Islamic Studies, 2019)
The use of funds that can make fund owners wealthier or more prosperous can decide to invest. The decision on the use of these funds is used in the company's operations in choosing the policy for the type of funds to be used. The important concept which is the basis for almost all decisions including in the field of financial management lies in the time value of money, in this case the concept of money value that is always used, namely in making decisions such asinvestment decisions, dividend policies, and spending decisions. Whereas in the theory of legitimacy revealed that every company or organization must have an assessment that is in line with the norm values of stakeholders or those found in society. Legitimacy can also end if it is unable to communicate all actions against maysrakat even though the company or organization has taken actions that are in line with the expectations of the community.